Experimental investigation of friction reduction: by superimposed vibrations. (2018) - Holl, Helmut J.; Meindlhumer, Martin; Simader, Viktoria; Schnürer, Dominik; Brandl, Andreas
Abstract: A friction force is present when surfaces in contact perform a relative motion. There are various friction phenomena depending on the contact condition and structure of the surface, friction force and wear. Energy dissipation and wear result from friction effects between the bodies in contact depending on the contact parameters. A reduction of the effects of friction is possible with suitable superimposed vibrations and relative motion. An experimental setup was designed and constructed to evaluate the possible reduction of friction forces by superimposing vibrations with a defined motion in a certain frequency range. Various frequencies and vibration amplitude parameters have been adjusted in the experimental setup and friction forces have been studied and analyzed. In the experimental setup additionally defined cutting forces are analyzed and separated from the friction forces. A high number of experiments has been performed in order to get a small variation and confidence interval of the results, where force and power consumption ratios have been analyzed.